2018
DOI: 10.1177/1049909118760302
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers’ Characterization of Conversations Following an ACP Event

Abstract: The ACP events promote conversation regarding quality of life, general wishes at the end of life, and specific medical wishes. Barriers to conversation following ACP were similar to barriers to ACP in general, suggesting that a more intentional focus on addressing these barriers pre- and post-ACP may be necessary to improve communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Some physicians in this study had prior experiences where patients had declined a decision-making conversation, but in an English study of severely ill COPD patients, 98 of 100 found EOL discussions appropriate [ 21 ]. In contrast, more families than patients seem uncomfortable talking about advanced care planning after it has been brought up by their physician [ 22 ], but still three out of four will address the subject several times with the patient afterwards [ 23 ]. Lack of clarity about the most appropriate timing has been found in other studies [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some physicians in this study had prior experiences where patients had declined a decision-making conversation, but in an English study of severely ill COPD patients, 98 of 100 found EOL discussions appropriate [ 21 ]. In contrast, more families than patients seem uncomfortable talking about advanced care planning after it has been brought up by their physician [ 22 ], but still three out of four will address the subject several times with the patient afterwards [ 23 ]. Lack of clarity about the most appropriate timing has been found in other studies [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This idea was stressed considering the difference between imagining being sick and being sick. In the participants’ opinions, this difference requires that someone can protect the will of the sick through clear and transparent communication with the family members and the medical team [ 64 , 65 , 66 ]. In particular, it was considered crucial to respect the decisions regarding therapies that require more invasive interventions, while palliative care was highly valued.…”
Section: Discussionmentioning
confidence: 99%
“…Advance directives are legal documents describing preferences for future care and appointing a surrogate to make health care decisions in the event of incapacity (2). Today, advance care planning and advance directives are conceptualized as a health behavior (3), and their benefits are demonstrated at the individual (e.g., reducing unnecessary pain, unhelpful or invasive procedures or unwanted hospitalizations), family (e.g., minimizing stress and burden, avoiding conflicts among family members, and providing peace of mind), physician (e.g., reducing conflicts and misunderstanding with family members, avoiding ethical dilemmas), and social levels (e.g., reducing health care costs) (4)(5)(6)(7)(8)(9). Given the characteristics of dementia (10), completing advance directives has been declared an essential instrument for preserving and respecting the autonomy and preferences for endof-life care of people with this disease (11).…”
Section: End-of Life and Advance Care Planningmentioning
confidence: 99%